Dental hygienist - Simon, Charnan (Mankato, Minn. : Capstone High/Low Books, 1998)
Outlines the educational requirements, duties, salary, employment outlook, and possible future positions of dental hygienists.
Includes bibliographical references and index.
Keywords: Dental hygiene -- Vocational guidance -- Juvenile literature